Validation of the National Institute of Neurological Disorders and Stroke Spinal Cord Injury MRI Common Data Elements Instrument - Fisher, J.; Krisa, L.; Middleton, D.M.; Leiby, B.E.; Harrop, J.S.; Shah, L.M.; Schwartz, E.D.; Doshi, A.; Faro, S.H.; Mohamed, F.B.; Flanders, A.E. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The National Institute of Neurological Disorders and Stroke common data elements initiative was created to provide a consistent method for recording and reporting observations related to neurologic diseases in clinical trials. The purpose of this study is to validate the subset of common data elements related to MR imaging evaluation of acute spinal cord injury.MATERIALS AND METHODS: Thirty-five cervical and thoracic MR imaging studies of patients with acute spinal cord injury were evaluated independently in 2 rounds by 5 expert reviewers. Intra- and interrater agreement were calculated for 17 distinct MR imaging observations related to spinal cord injury. These included ordinal, categoric, and continuous measures related to the length and location of spinal cord hemorrhage and edema as well as spinal canal and cord measurements. Level of agreement was calculated using the interclass correlation coefficient and kappa.RESULTS: The ordinal common data elements spinal cord injury elements for lesion center and rostral or caudal extent of edema or hemorrhage demonstrated agreement ranging from interclass correlation coefficient 0.68 to 0.99. Reproducibility ranged from 0.95 to 1.00. Moderate agreement was observed for absolute length of hemorrhage and edema (0.54 to 0.60) with good reproducibility (0.78 to 0.83). Agreement for the Brain and Spinal Injury Center score showed the lowest interrater agreement with an overall kappa of 0.27 (0.20, 0.34). For 7 of the 8 variables related to spinal cord injury, agreement improved between the first and second evaluation. Continuous diameter measures of the spinal cord and spinal canal using interclass correlation coefficient varied substantially (0.23 to 0.83).CONCLUSIONS: Agreement was more consistent for the ordinal measures of spinal cord injury than continuous measures. Good to excellent agreement on length and location of spinal cord hemorrhage and edema can be achieved with ordinal measures alone.BASICBrain and Spinal Injury CenterCDEcommon data elementCRFcase report formNINDSNational Institute of Neurological Disorders and StrokeSCIspinal cord injuryICCinterclass correlation coefficient